Intestinal tuberculosis versus Inflammatory Bowel Diseases: a never-ending challenge - Castellotti, Paola; Riccardi, Niccolò; Ferrarese, Maurizio; Canetti, Diana; Fanti, Diana; ti, Edoardo; Reda, Marco; Alexiadis, Spyridon; Bonoldi, Emanuela; Saporiti, Matteo; Perno, Carlo Federico; Ruffo Codecasa, Luigi (The New microbiologica, 2020)
Inflammatory Bowel Diseases (IBD) and intestinal tuberculosis (ITB) frequently share similar clinical, radiological, endoscopic and histologic features. The misdiagnosis of IBD can lead to worsening of ITB course, eventually with dissemination of Mycobacterium tuberculosis (MTB) due to immunosuppressive treatment. We herein report a challenging diagnosis of ITB, progressed from localized to disseminated, in a pregnant woman previously misdiagnosed with Crohn' disease (CD) on prolonged steroid treatment. Furthermore, we focus on three main issues: 1) the need for tuberculosis (TB) screening in pregnant women and in patients coming from TB endemic countries; 2) the effect of prolonged steroid treatment in misdiagnosed TB, particularly on its histological pattern; 3) the optimum clinical management of ITB.Inflammatory Bowel Diseases (IBD) and intestinal tuberculosis (ITB) frequently share similar clinical, radiological, endoscopic and histologic features. The misdiagnosis of IBD can lead to worsening of ITB course, eventually with dissemination of Mycobacterium tuberculosis (MTB) due to immunosuppressive treatment. We herein report a challenging diagnosis of ITB, progressed from localized to disseminated, in a pregnant woman previously misdiagnosed with Crohn' disease (CD) on prolonged steroid treatment. Furthermore, we focus on three main issues: 1) the need for tuberculosis (TB) screening in pregnant women and in patients coming from TB endemic countries; 2) the effect of prolonged steroid treatment in misdiagnosed TB, particularly on its histological pattern; 3) the optimum clinical management of ITB.